EP-422 Operating in the outpatient department: the future of flexor tendon repair?. (9th August 2022) - Rayner, Anthony; Mohamed, Ahmed; Mikhail, Mark; Gardiner, Matthew
Abstract: Aims: Flexor tendon injuries are debilitating with rupture of repair leading to significant morbidity. The SARS-CoV-2 pandemic has led to a shift to out-of-theatre operating, with many flexor tendon repairs being performed on the same day as initial assessment in our outpatient department (OPD) procedure room. We aimed to compare the rupture rates before and after the start of the pandemic to assess the safety of this change in practice. Methods: Patients who underwent repair of one or more flexor tendons were included from two six-month periods: July to December 2019 and April to September 2020. Patient records were reviewed to identify operation location, number of flexor tendons repaired per patient and rupture incidence. In the second period, patients whose operation was performed in theatre were excluded. Results: 28 patients were included for the initial period with a total of 49 flexor tendons injured. All repairs were performed in theatre and 3 ruptures were recorded (6%). 17 patients underwent flexor tendon repair during the second period. 11 patients were operated on in the OPD with a total of 16 flexor tendons injured. 1 rupture was recorded (6%). Conclusions: The rupture rate of OPD operating is comparable to that of the traditional theatre pathway. OPD operating also allowed us to circumvent theatre waiting lists and thus avoid costly delays to patient care. This project demonstrates maintained safety for patients and offers a platform for further research to confirm OPD operating as a viable and sustainable alternative for future practice.